FIT2 proteins and lipid droplet emergence, an interplay between phospholipid synthesis, surface tension, and membrane curvature - Graff, Juliette; Schneiter, Roger (Frontiers in Cell and Developmental Biology, 2024)
Lipid droplets (LDs) serve as intracellular compartments primarily dedicated to the storage of metabolic energy in the form of neutral lipids. The processes that regulate and control LD biogenesis are being studied extensively and are gaining significance due to their implications in major metabolic disorders, including type 2 diabetes and obesity. A protein of particular interest is Fat storage-Inducing Transmembrane 2 (FIT2), which affects the emergence step of LD biogenesis. Instead of properly emerging towards the cytosol, LDs in FIT2-deficient cells remain embedded within the membrane of the endoplasmic reticulum (ER). In vitro studies revealed the ability of FIT2 to bind both di- and triacylglycerol (DAG/TAG), key players in lipid storage, and its activity to cleave acyl-CoA. However, the translation of these in vitro functions to the observed embedding of LDs in FIT2 deficient cells remains to be established. To understand the role of FIT2 in vivo, we discuss the parameters that affect LD emergence. Our focus centers on the role that membrane curvature and surface tension play in LD emergence, as well as the impact that the lipid composition exerts on these key parameters. In addition, we discuss hypotheses on how FIT2 could function locally to modulate lipids at sites of LD emergence.